Epididymal and testicular sperm for intracytoplasmic sperm injection in the treatment of obstructive azoospermia - Björn Rosenlund; Peter Sjöblom; Anna Dimitrakopoulos; Torbjörn Hillensjö (Acta Obstetricia et Gynecologica Scandinavica)
Background. The possibility of treating male infertility because of obstructive azoospermia has been poor, but intracytoplasmic sperm injection (1CSI) has given this type of infertility sufferer a new option. Material and methods. In this study 13 couples with obstructive azoospermia were treated in a total of 19 stimulated IVF cycles. The men were between 27 and 45 (mean 33) years of age. Their partners, 24–39 (mean 31) years of age were treated according to routine IVF procedures, i.e. down regulation with buserelin followed by hyperstimulation with urofollitropin. Fertilization was obtained by ICSI. Two embryos were transferred on day two after the ovum pick up. Sperm were retrieved through microsurgical epididymal aspiration (MESA) in four cycles, percutaneous epididymal sperm aspiration (PESA) in three cycles and through testicular sperm extraction (TESE) in 12 cycles. Results. The overall fertilization rate was 68%, with a cleavage rate of 82%. The fertilization rate was equal (68%) with epididymal and testicular sperm and the cleavage rate was 87% and 80%, respectively. Embryos were obtained for embryo transfer (ET) in all cases and five pregnancies (one twin pregnancy) were established (26% per ET), three using epididmal sperm and two using testicular sperm. Conclusion. Infertility due to obstructive azoospermia can successfully be treated with epididymal sperm and ICSI. When epididymal sperm cannot be found sperm extracted from a testicular biopsy can be used. PESA and TESE are quicker and easier alternatives to MESA and can be performed on an outpatient basis with local anesthesia.